#### Answer

1

#### Work Step by Step

$(xz-5)^4$ $\longrightarrow$ substitute
=$(2(3)-5)^4$ $\longrightarrow$ solve expression in parenthesis
=$(6-5)^4$
=$1^4$$\longrightarrow$ solve exponent
=$1$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.